Effect of Eight Weeks of Selected Corrective Exercises on Strength and Range of Motion of Shoulder Rotation in Male Boxers With Scapular Dyskinesis - Soroush Momenpour; Seyed Hosein Hoseini; Hasan Daneshmandi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims In previous studies, different results have been reported regarding the effect of corrective exercises on improving scapular dyskinesis and its related symptoms. The present study aims to investigate the effect of eight weeks of selected corrective exercises on strength and range of motion (ROM) of shoulder rotation in male boxers with scapular dyskinesis.Methods This is a quasi-experimental study that was conducted on 30 male boxers in Guilan province of Iran including 15 in the control group (age: 24.05±3.80 years; weight: 73.54±5.52 kg; height: 177.18±5.08 cm) and 15 in the exercise group (age: 25.01±4.05 years; weight: 74.14±6.31 kg; height: 176.69±5.14 cm). The boxers in the exercise group performed selected corrective exercises for 8 weeks (strengthening the serratus anterior and middle retractors and stretching the pectoralis minor). Diagnosis and severity of scapular dyskinesis was measured by the lateral scapular slide test. The ROM of shoulder rotation was measured using a manual goniometer, and the shoulder rotation strength was assessed using a manual dynamometer. All tests were performed in pre-test and post-test phases. Statistical analyses were performed using paired t-test and analysis of covariance. The significance level was set at 0.05.Results The selected corrective exercises had a significant effect on improving scapular dyskinesia and the external rotation strength of the shoulder in the exercise group compared to the control group (P≤0.05), but had no significant effect on improving the internal rotation strength of the shoulder and the ROM of shoulder rotation (P>0.05)Conclusion The selected corrective exercises can improve scapular dyskinesis and increasing the external rotation strength of the shoulder in male boxers with scapular dyskinesis. Therefore, trainers, athletes and therapists can use these exercises to reduce the symptoms related to this disorder and improve performance of boxers with scapular dyskinesis.